Efficiency of injected anchors in masonry elements: Evaluation of pull-out strength. (18th January 2021) - Ceroni, Francesca; Darban, Hossein; Caterino, Nicola; Luciano, Raimondo
Highlights: Numerical pull-out force database for different injected anchors in masonry. Calibration of a strength model for predicting maximum pull-out forces. Proposal of average and 5% percentile provisions for maximum pull-out forces. Acceptable predictions of proposed model compared to experimental results. Abstract: Injected anchors in masonry elements represent a widespread technique for improving the 'box behavior' of masonry structures, since they contribute to avoid or delay out-of-plane mechanisms under horizontal actions. Despite of their diffusion, no clear design indications for injected anchors are available in literature and codes. This paper is aimed to propose design formulations for the maximum pull-out force in injected anchors basing on wide numerical analyses realized through a 2D Finite Element (FE) model specifically tuned to simulate pull-out tests. Thanks to the variation of several parameters, the most significant ones influencing the maximum pull-out force are identified and introduced in the strength models and several coefficients are assessed through best fitting regression analyses carried out on the numerical results. Finally, based on a 'design by testing' approach, preliminar 5% percentile provisions for the maximum pull-out force are proposed too, and the reliability of the 'design-oriented' formulation is assessed by means of comparisons with experimental results of some pull-out tests available in literature.